The Mapping of Tax Compliance Research in Indonesia - Risca Novita Sari; Nurul Herawati; Nur Farahah Mohd Pauzi (Universitas Negeri Padang, 2023)
Purpose – This study aims to review the development of tax research, especially tax compliance in Indonesia for 22 years. Design/methodology/approach – The review is based on 129 tax compliance articles published in Indonesian accredited scientific journals Science and Technology Index (Sinta) 1 and 2 and/or A and B in 2001 – 2022. Tax compliance articles were selected with the keywords “tax compliance,” “tax non-compliance,” “tax compliance taxpayer,